Subjective Aspects of Breastfeeding and Weaning: Evidence from Three Cases - Ferrari, Andrea Gabriela (2017)
This study aimed to investigate subjective aspects of breastfeeding and weaning at three and eight months of baby’s life. A longitudinal multiple case study design was used. Three primiparous mothers were interviewed about various aspects of motherhood, in particular, breastfeeding and weaning. Analysis of qualitative content of maternal responses, based on psychoanalysis, revealed that breastfeeding can be an indication of an incestuous mother-infant relationship in which this can be taken as the object of maternal desire. Mothers also reported the experiences of pleasure and displeasure associated with breastfeeding, highlighting the existing difficulties and ambiguities present. Thus, the study indicates that breastfeeding and weaning encompass meanings and implications beyond the biological, referring to the mother-child relationship, as well as the mother’s constitutive story.